IMPROVEMENT OF THE SIMP METHOD FOR TOPOLOGY OPTIMIZATION OF LOAD‑BEARING ELEMENTS OF FOREST MACHINERY STRUCTURES - Pyshka, Roman; Bakay, Borys (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The paper presents an improved topology optimization method, FA-SIMP, for the design of load-bearing structural components of forest harvesting machines, in particular manipulator brackets of forwarders. The aim of the work is to reduce the mass of parts without compromising stiffness and to improve their fatigue life by enhancing the convergence of the classical SIMP method. The FA‑SIMP algorithm integrates the acceleration step (lookahead) into the classical SIMP scheme, allowing gradients to be computed in a more promising optimization direction. A numerical experiment was conducted using a 2D plane-stress beam model (340×80 mm, thickness 10 mm) made of steel (E=210 GPa, ν=0.30), loaded with a concentrated force of 5.0 kN at a prescribed material volume of 40%. The finite element mesh consisted of 7200 elements. The results showed that, for 120 iterations, FA‑SIMP reduces structural compliance (C=7.181 J vs. 7.206 J) and reduces the von Mises peak stress by 2.64% (159.09 MPa vs. 163.4 MPa) compared to the classical SIMP. The grey index of the final topology decreased from 0.1964 to 0.1591, which simplifies the transition to manufacturing documentation. Implementing the FA‑SIMP method in the design practice of load‑bearing elements of forest machinery can reduce the specific ground pressure, fuel consumption and carbon footprint of timber harvesting operations, which is consistent with the principles of sustainable forest management.